2022
DOI: 10.3390/agronomy12020360
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Content Directly Affects Bud Burst Rate in Single-Node Cuttings of Perennial Plants

Abstract: The use of single-node cuttings of shoots as explants to study bud dormancy and its physiology under controlled conditions is a common practice in grapevine (Vitis vinifera L.) or other perennial plant research. In particular, this method has been extensively used to understand the effect of different chemicals on bud dormancy and bud burst. However, the soil water content in those experiments is usually not reported and its relevance is often neglected. Here, we observed that an unevenly distributed soil wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…However, in a different context, a similar message is obtained from the work reported by Signorelli et al [10], who evaluated the effect of soil water content on bud burst rate using grapevine single node cuttings. The authors showed that soil water content (% of field capacity) significantly affects bud burst rate, concluding that soil water content has to be controlled to assess bud burst in perennial plants.…”
supporting
confidence: 62%
“…However, in a different context, a similar message is obtained from the work reported by Signorelli et al [10], who evaluated the effect of soil water content on bud burst rate using grapevine single node cuttings. The authors showed that soil water content (% of field capacity) significantly affects bud burst rate, concluding that soil water content has to be controlled to assess bud burst in perennial plants.…”
supporting
confidence: 62%
“…Drought is one of the many factors with a negative effect on the morphology, physiology, and development of plants of the economically important oilseed rape [ 27 , 28 ]. Previous studies have shown that water deficit induces metabolic changes in plants that lead to the accumulation of specific metabolites such as proline [ 29 , 30 , 31 ]. Moreover, data from the literature indicate that exogenous application of osmoprotectants has shown positive effects on plants growing under drought stress, promoting growth and antioxidant activity [ 17 , 32 ].…”
Section: Discussionmentioning
confidence: 99%